The investigation of hypocalcaemia and rickets. Issue 5 (1st May 2003) - Singh, J; Moghal, N; Pearce, S H S; Cheetham, T
Abstract : Our understanding of disorders that present with hypocalcaemia has advanced rapidly in the past decade. The molecular basis of many of these disorders and conditions associated with phosphate wasting has now been established. While many children will need specialist involvement, they often will present to general paediatricians, and appropriate investigations prior to intervention will enable early diagnosis. Not all children with hypocalcaemia and low or low normal parathyroid hormone levels have isolated hypoparathyroidism, and clinicians need to be aware of the potential for misdiagnosis. Outpatient departments and paediatric wards should have a readily accessible and comprehensive list of bloods that need to be taken when a child presents with hypocalcaemia or rickets.